2019
DOI: 10.9734/isrr/2019/v8i130093
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Barriers and Determinants of Prevention of Mother to Child Transmission (PMTCT) of Human Immune Deficiency Virus (HIV) Services at Public Teaching Hospitals in Enugu State, Nigeria

Abstract: Introduction: The most effective means of reducing Mother-to-Child transmission of HIV is to provide suppressive HAART. Prevention of Mother to Child Transmission (PMTCT) directly affects the achievement of Sustainable Development goals just. The unmet need for PMTCT services in Nigeria, particularly in Enugu state, is unacceptably high. This study aimed to assess factors associated with access barriers and determinants to PMTCT services in public health facilities in Enugu, Nigeria. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“… 18 Prevention of mother-to-child transmission of HIV is our golden opportunity to reduce and eliminate the passing of HIV from the mother to her child because 90% of the total HIV infection in Africa are caused by MTCT. 19 Different kinds of the literature showed that the infrastructures of any health institution’s staffing of facilities and capabilities of its staff, adequate and ventilated rooms for privacy, the policy environment in which care is delivered, and the availability of resources of the institution should be fulfilled and be monitored closely. 20–23 To overcome these problems, several strategic plans should be investigated in the form of evaluation.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Prevention of mother-to-child transmission of HIV is our golden opportunity to reduce and eliminate the passing of HIV from the mother to her child because 90% of the total HIV infection in Africa are caused by MTCT. 19 Different kinds of the literature showed that the infrastructures of any health institution’s staffing of facilities and capabilities of its staff, adequate and ventilated rooms for privacy, the policy environment in which care is delivered, and the availability of resources of the institution should be fulfilled and be monitored closely. 20–23 To overcome these problems, several strategic plans should be investigated in the form of evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The health practitioners' negative attitudes toward mothers after missing an appointment added to their reluctance to return. Negative attitudes of health care workers have been reported as an adherence barrier in other studies in Sub-Saharan Africa (Kate et al, 2019; Mbeya Munkhondya et al, 2021; Nkwabong et al, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…return. Negative attitudes of health care workers have been reported as an adherence barrier in other studies in Sub-Saharan Africa (Kate et al, 2019;Mbeya Munkhondya et al, 2021;Nkwabong et al, 2018).…”
Section: The Need For Flexible Health Facility Accessmentioning
confidence: 87%
See 1 more Smart Citation
“…Wachira et al showed that disclosure of the HIV-positive status for both mothers and children was associated with stigma based on family opinions and conflict, resulting in non-enrollment of children. [ 11 ] Similarly, several researchers [ 21 , 24 , 25 ] have documented stigma and discrimination as significant barriers to accessing HIV services among children.…”
Section: Discussionmentioning
confidence: 99%